1997
DOI: 10.1111/0004-5608.872057
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Persistent Ambiguity of GIS as ‘Tool’ versus ‘Science’

Abstract: Is GIS a tool or a science? The question is clearly important in the day-to-day operations of geography departments. Departments need to know if GIS is a tool that should be taught at the undergraduate level, or a science and thus a legitimate research specialty of faculty and graduate students. We summarize the debate on this question that was conducted on GIS-L electronic listserver in late 1993. In evaluating this discussion it became clear that GIS could be understood not by the two distinct positions take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(110 citation statements)
references
References 31 publications
0
101
0
4
Order By: Relevance
“…This is an important part of geographic information science that concerns itself with the implications of geographic information (system) use within organizations, community, and society. The study reported in this article fuels the discourse about the role of GIS as "tool or science" (Pickles 1996;Wright, Goodchild, and Proctor 1996a), but along different emphases from those articulated in the discourse to date. Wright, Goodchild, and Proctor (1996a) provide a service to GIS researchers by writing about the multiple roles of GIS, which is sometimes viewed as a tool and sometimes viewed as a science.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…This is an important part of geographic information science that concerns itself with the implications of geographic information (system) use within organizations, community, and society. The study reported in this article fuels the discourse about the role of GIS as "tool or science" (Pickles 1996;Wright, Goodchild, and Proctor 1996a), but along different emphases from those articulated in the discourse to date. Wright, Goodchild, and Proctor (1996a) provide a service to GIS researchers by writing about the multiple roles of GIS, which is sometimes viewed as a tool and sometimes viewed as a science.…”
mentioning
confidence: 83%
“…The study reported in this article fuels the discourse about the role of GIS as "tool or science" (Pickles 1996;Wright, Goodchild, and Proctor 1996a), but along different emphases from those articulated in the discourse to date. Wright, Goodchild, and Proctor (1996a) provide a service to GIS researchers by writing about the multiple roles of GIS, which is sometimes viewed as a tool and sometimes viewed as a science. Like Pickles (1996), however, we doubt the usefulness of an analysis of e-mail dialogue about GIS as "tool or science," as reported by Wright, Goodchild, and Proctor (1996a) because of a lack of reflective thought on the topic in terms of theoretical and philosophical grounding.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The incorporation of socioeconomic, natural, and administrative data in such a system permits: different criteria, to be assessed using integrative multi-criteria evaluation techniques (Jankowski 1995); the handling and manipulation of results, in order to make better decisions about the best preventive measures in the short, medium, and long run; and the possibility to progress as a legitimate scientific field in its own right (Wright et al 2004). The functional and applied capabilities of a GIS can provide data handling solutions possible at desktop level, which also facilitate decision making at more precise spatial scales, leading to advances in other decision making tools, for example, concerning transportation systems (O'Sullivan et al 2000).…”
Section: Regional Geographic Information Systemmentioning
confidence: 99%
“…In this context, the development and analysis of such a tool in GIS research can be seen as toolmaking, where end users can only benefit from the engineering of better tools [Wright et al, 1997], especially when it concerns a representation as prevalent as planar partitions.…”
Section: "What Benefits Does Using a Constrained Triangulation Bring mentioning
confidence: 99%